Effect of Fucoidan on the Mitochondrial Membrane Potential (ΔΨm) of Leukocytes from Patients with Active COVID-19 and Subjects That Recovered from SARS-CoV-2 Infection - Díaz-Resendiz, Karina Janice Guadalupe; Covantes-Rosales, Carlos Eduardo; Benítez-Trinidad, Alma Betsaida; Navidad-Murrieta, Migdalia Sarahy; Razura-Carmona, Francisco Fabian; Carrillo-Cruz, Christian Daniel; Frias-Delgadillo, Edwin Jaime; Pérez-Díaz, Daniela Alejandra; Díaz-Benavides, Matxil Violeta; Zambrano-Soria, Mercedes; Ventura-Ramón, Guadalupe Herminia; Romero-Castro, Aurelio; et al. (Marine drugs, 2022)
Fucoidan is a polysaccharide obtained from marine brown algae, with anti-inflammatory, anti-viral, and immune-enhancing properties, thus, fucoidan may be used as an alternative treatment (complementary to prescribed medical therapy) for COVID-19 recovery. This work aimed to determine the ex-vivo effects of treatment with fucoidan (20 µg/mL) on mitochondrial membrane potential (ΔΨm, using a cationic cyanine dye, 3,3′-dihexyloxacarbocyanine iodide (DiOC6(3)) on human peripheral blood mononuclear cells (HPBMC) isolated from healthy control (HC) subjects, COVID-19 patients (C-19), and subjects that recently recovered from COVID-19 (R1, 40 ± 13 days after infection). In addition, ex-vivo treatment with fucoidan (20 and 50 µg/mL) was evaluated on ΔΨm loss induced by carbonyl cyanide 3-chlorophenylhydrazone (CCCP, 150 µM) in HPBMC isolated from healthy subjects (H) and recovered subjects at 11 months post-COVID-19 (R2, 335 ± 20 days after infection). Data indicate that SARS-CoV-2 infection induces HPBMC loss of ΔΨm, even 11 months after infection, however, fucoidan promotes recovery of ΔΨm in PBMCs from COVID-19 recovered subjects. Therefore, fucoidan may be a potential treatment to diminish long-term sequelae from COVID-19, using mitochondria as a therapeutic target for the recovery of cellular homeostasis.